Irony in three short stories of Pilar Dughi’s Ave de la noche (Bird of the Night) - Chamorro Zuñiga, Diego Alessandro (2023)
This paper will approach the stories «Tomando el sol en el club», «Dime sí» and «Futuro prometido», from the book Ave de la noche (1996) by Pilar Dughi, from the perspective of irony. In this way, we argue that these stories show accentuated ironic forms of fate and character, developed by Peter Roster. It is about three levels proposed by Lauro Zavala (propositional, casuistic, and dialogic) on the ironic presentation of literary works. We will also cover four fundamental points: first, we will review the works that were carried out around Pilar Dughi’s stories and the irony in Peruvian literary stories close to the author; second, we will detail irony and its forms that make possible the analysis in literary texts according to Roster and Zavala; Thirdly, we will make a brief introduction to the literary figure of Pilar Dughi and we will present the stories of our interest; finally, the suggested stories will be analyzed according to irony and its guidelines already established in point two, to corroborate its fundamental presence in these stories.